Perbedaan Massage Payudara dengan Teknik “Z” Dan “Buku Jari Tangan” Terhadap Produksi ASI - Ana Rofika; Uswatun Kasanah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: The decrease in breast milk production in the first days after giving birth can be caused by a lack of stimulation of the hormones oxytocin and prolactin which play a very important role in the smooth flow of breast milk, causing breast milk not to come out immediately after giving birth, the baby having difficulty sucking because the mother's nipples are not supported. Currently, in midwifery services, complementary-based services have emerged which are often performed, including breast massage to overcome irregularities in breast milk production. Breast massage is breast massage, which is gentle massaging of the breasts which can be done every day. This study aims to determine the difference between breast massage using the